One hundred and fyfty years of combustion of fossil hydrocarbons: the emergent alternatives (2009)
After one hundred and fifty years of having drilled the first commercial oil wells that led to the intensive use of liquid fuels to move transport vehicles, it is reaching the peak of the planet's oil reserves. There is still a good portion to spend, with the expectation that the consequences will be better than in the first part, which has involved several wars and environmental damage. This essay provides a summary of the history of fossil fuels and the prospect of emerging energy alternatives, emphasizing bioenergy as an alternative for the transition between the current era of combustion and the new era of clean energy.